Analysis of the Effect of Non-Performing Loans, Loan to Deposit Ratio, and Capital Adequacy Ratio on Book Value per Share through Return on Assets Mediation - Yandi Asmana; Hari Gusrida; Yohanes Indrayono (Greenation Research & Yayasan Global Resarch National, 2026)
This study examines the effect of Non-Performing Loans (NPL), Loan-to-Deposit Ratio (LDR), and Capital Adequacy Ratio (CAR) on firm value proxied by Book Value per Share (BVS), with Return on Assets (ROA) as a mediating variable in banking companies listed on the Indonesia Stock Exchange during 2015–2024. This research employs a quantitative approach using panel data regression. The sample consists of 11 banks selected through purposive sampling, resulting in 110 observations. Data analysis was conducted using EViews 12 and the Sobel test to examine the mediation effect. The results show that NPL has a negative and significant effect on ROA and BVS. LDR has no significant effect on ROA but positively affects BVS. CAR has a positive effect on both ROA and BVS. Furthermore, ROA significantly increases BVS. Mediation analysis indicates that ROA does not mediate the effect of NPL and LDR on BVS but mediates the relationship between CAR and BVS. These findings highlight the importance of credit risk management, effective intermediation, and strong capital structures in enhancing banking firm value.